Prisma e pirâmide: um estudo didático de uma abordagem computacional - Ferraz, Marcelo Cardoso (2010)
In the preliminary studies, moreover, in the bibliográphy revision, it's been observed that some works report difficulties that teachers might find when teaching the content: prism and pyramid volumes. Aiming the deepening of the knowledge related to the studies of prism and pyramid volume and aware that the theme still needs reaserch, it's been considered as an hypothesis at this study that a teaching sequence conceived by the Theory of Didatic Situations and the Theory of Registry of semioptical Representations, done by the use of a dynamic geometry software, Cabri 3D, could contribute to deepen the study on the theme. The objective of the rersearch was to develop a teaching sequence to deepen the study with teachers currently in the public network tha would allow the development of the ability to express algebrically and graphically the volume of prisms and pyramids, favoring the greatness chart. After the elaboration, the prior analysis of the sequence and sbjecting that to a group of Mathematics teachers from the board of the Public Teaching Department of Jacareí, The posteriori analysis showed that our hypothesys had been confirmed, that is, that a sequence developed and applied based on the Theory of Didatic Situations and on the change of registry of representation conduct the teachers to recognizing the volume of prisms and pyramids as greatnesses